A prenatal prediction model for total nucleated cell count increases the efficacy of umbilical cord blood banking. Issue 11 (28th April 2014) - Manegold‐Brauer, Gwendolin; Borner, Barbara; Bucher, Christoph; Hoesli, Irène; Passweg, Jakob; Girsberger, Sabine; Schoetzau, Andreas; Gisin, Simona; Visca, Eva
<x xml:space="preserve">Abstract</x> Background The most important factor for the selection of an umbilical cord blood unit (CBU) for hematopoietic stem cell transplantation is the total nucleated cell (TNC) count as a surrogate marker for stem cell content in the CBU. At present, about one in five donors can provide a CBU with a sufficient TNC count for umbilical cord blood (UCB) banking. It is labor‐intensive to obtain consent of all eligible donors and optimization of the selection is needed. The purpose of this study was to investigate prenatal clinical predictors for TNC count that would help to identify successful UCB donors already on admission to the delivery unit. Study Design and Methods This study was a retrospective analysis of 758 cryopreserved CBUs, collected from 2002 to 2006. Maternal and fetal factors analyzed were maternal age, gravidity, parity, weight, height, diabetes, premature rupture of membranes, gestational age, fetal sex, and birthweight. The impact on a high TNC count (<150 × 107 vs. ≥150 × 107) of the CBU was modeled in a multivariate analysis model. Results Fetal birthweight was the strongest predictor (p < 0.001) of TNC count of at least 150 × 107. With a composite score of parity, gestational week, maternal weight and height, fetal sex, and birthweight, a nomogram was developed that increased banking rates from 22.7% to 31.9% while decreasing the number of banked CBUs from 149 to 79. Conclusions Our prenatal prediction model increases the efficacy of obtaining informed consent for UCB banking while still allowing relevant numbers of CBUs to be banked.